A Novel Homozygous Frameshift Variant in XYLT2 Causes Spondyloocular Syndrome in a Consanguineous Pakistani Family - Kausar, Mehran; Chew, Elaine Guo Yan; Ullah, Hazrat; Anees, Mariam; Khor, Chiea Chuen; Foo, Jia Nee; Makitie, Outi; Siddiqi, Saima (Frontiers in Genetics, 2019)
We report on three new patients with spondyloocular syndrome (SOS) in a consanguineous Pakistani family. All three patients present progressive generalized osteoporosis, short stature, recurrent fractures, hearing loss and visual impairments. WES revealed a novel homozygous frameshift variant in exon 11 of XYLT2 (NG 012175.1, NP_071450.2) resulting in loss of evolutionary conserved aminoacid sequences (840 – 865/865) at C-terminus p.C840fs*115. Sanger Sequencing confirmed the presence of the novel homozygous mutation in all three patients while the parents were heterozygous carriers of the mutation, in accordance with an autosomal recessive inheritance pattern. Only nine variants worldwide have previously been reported in XYLT2 in patients with SOS phenotype. These three patients with novel homozygous variant extend the genotypic and phenotypic spectrum of SOS.